An outbreak of illness among schoolchildren in London: toxic poisoning not mass hysteria. - Aldous, J C (1994)
STUDY OBJECTIVE--To determine the cause of an outbreak of acute gastrointestinal illness that occurred shortly after lunch in children attending a school in London, UK. DESIGN--A questionnaire survey of children at the affected school was carried out on the day after the incident. Microbiological, environmental, and toxicological investigations were also undertaken. SETTING--A school in London, UK. PARTICIPANTS--Altogether 374/468 (80%) of the children who had eaten lunch at the school on the day of the incident completed a questionnaire. MAIN RESULTS--There was a significant association between illness and the consumption of raw cucumber (relative risk = 6.1; 95% confidence interval 2.2, 16). Microbiological investigation of the foods served at lunch did not show any pathogens and toxicological investigations suggested that the cucumbers were contaminated by a pesticide. CONCLUSIONS--Although the outbreak displayed several typical features of mass psychogenic illness, the most probable cause was a toxic chemical present in cucumber served at lunch. Those responsible for investigating outbreaks of illness should be aware of the possible toxicological causes and the appropriate modes of investigation. They should be wary of too readily attributing a psychogenic cause to unusual outbreaks of acute illness in schoolchildren.